Leishmania chitinase facilitates colonization of sand fly vectors and enhances transmission to mice - Rogers, Matthew E (Blackwell Publishing Ltd, 2008)
Chitinases of trypanosomatid parasites have been proposed to fulfil various roles in their blood-feeding arthropod vectors but so far none have been directly tested using a molecular approach. We characterized the ability of Leishmania mexicana episomally transfected with LmexCht1 (the L. mexicana chitinase gene) to survive and grow within the permissive sand fly vector, Lutzomyia longipalpis. Compared with control plasmid transfectants, the overexpression of chitinase was found to increase the average number of parasites per sand fly and accelerate the escape of parasites from the peritrophic matrix-enclosed blood meal as revealed by earlier arrival at the stomodeal valve. Such flies also exhibited increased damage to the structure of the stomodeal valve, which may facilitate transmission by regurgitation. When exposed individually to BALB/c mice, those flies with chitinase-overexpressing parasites spent on average 2.4–2.5 times longer in contact with their host during feeding, compared with flies with control infections. Furthermore, the lesions that resulted from these single fly bite infections were both significantly larger and with higher final parasite burdens than controls. These data show that chitinase is a multifunctional virulence factor for L. mexicana which assists its survival in Lu. longipalpis. Specifically, this enzyme enables the parasites to colonize the anterior midgut of the sand fly more quickly, modify the sand fly stomodeal valve and affect its blood feeding, all of which combine to enhance transmission.